2001
DOI: 10.1590/s1516-14392001000300014
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 thin film growth using the MOCVD method

Abstract: Titanium oxide (TiO2) thin films were obtained using the MOCVD method. In this report we discuss the properties of a film, produced using a ordinary deposition apparatus, as a function of the deposition time, with constant deposition temperature (90 °C), oxygen flow (7,0 L/min) and substrate temperature (400 °C). The films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM) and visible and ultra-violet region spectroscopy (UV-Vis). The films deposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 21 publications
1
17
1
1
Order By: Relevance
“…The R a values of the single-layer and three-layer sol-gel TiO 2 films without PEG are 2.10 ± 0.02 nm and 5.11 ± 0.04 nm, respectively. The R a values were lower than those reported in the literature [25][26][27], indicating a possibility that the films are optically smooth [25]. The lower roughness value represents good homogeneity of the TiO 2 particles on the surface [28].…”
Section: Afm Analysismentioning
confidence: 60%
“…The R a values of the single-layer and three-layer sol-gel TiO 2 films without PEG are 2.10 ± 0.02 nm and 5.11 ± 0.04 nm, respectively. The R a values were lower than those reported in the literature [25][26][27], indicating a possibility that the films are optically smooth [25]. The lower roughness value represents good homogeneity of the TiO 2 particles on the surface [28].…”
Section: Afm Analysismentioning
confidence: 60%
“…Moreover, it also indicates that the OH groups on the silica network are condensing to form Si-O-Si bridges resulting in the weight loss. It has been previously reported that the weight loss at temperatures lower than 270 °C in composites is due to the removal of physically absorbed water molecules [34][35][36][37]. While, in the case of heat treated sample, the first regime corresponds to removal of solvent residues and adsorbed water.…”
Section: Page 7 Of 30mentioning
confidence: 96%
“…XRD pattern contains diffraction peaks for both PbS as well as TiO2. The diffraction peaks corresponding to reflection from (044), (200) and (311) planes of TiO2 [10]. [11].…”
Section: Xrdmentioning
confidence: 99%